Numerical Notation in Africa - Rovenchak, Andrij (AAeO - Afrikanistik-Aegyptologie-Online, 2012)
Systems of numerical notations used in Africa from the Ancient Egypt till modern time are reviewed. Tables of symbols are presented. Basic principles of numeral representation are briefly described.